Peran Ibu Single Parent dalam Proses Pembentukan Karakter Anak - Yogi Nurfauzi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2016)
Abstract: The role of single parent mother is important in the formation of character. There are numerous single parent mothers after diverce of death of the husband. raising children without the help of partners. Single parent mother role is critical in shaping the character of children of children. At least there five guidance of single parent mother in shaping the children’s character. First, the guidance of thought, Second, cultural guidance. Third, social guidance. Fourth, moral guidance. Fifth, religious guidance. Keywords: Mother, Single Parent, Character, Guidance.